The determinan of work discipline and competence on employee performance on PT XYZ (Sugar Industry) - Alviosa Rifa Debian; Yayan Firmansyah (Institute of Computer Science (IOCS), 2023)
The phenomenon in this study is in the form of inconsistent employee performance appraisals, an increase in the number of absenteeism of employees, and employee competency assessments that do not match the set targets. The purpose of this study was to determine the effect of work discipline on employee performance, competency on employee performance, and work discipline and competence on employee performance. There is a research gap from several previous studies which states that the results in this study have an influence or no effect on the variables studied, so this research has an urgency to re-examine the relationship between work discipline and competence on employee performance. This research uses the quantitative method. The population of this study was PT XYZ employees, totaling 411 people, and with a sample using the Slovin technique, a sample of 204 people was obtained. The data analysis technique used in this study is multiple linear regression analysis. The results of the study, namely H1, are accepted, stating that work discipline has a significant and positive influence with a percentage of 11.4%, and the remaining 88.6% is influenced by other variables. In H2 the competency variable has a significant and positive influence on employee performance with a percentage of 31.3% and the remaining 68.7% is influenced by other variables. In H3 the hypothesis is accepted that work discipline and competence simultaneously have an influence on employee performance with a percentage of 34.5% and the remaining 65.5% is influenced by other variables such as leadership, corporate culture, compensation, and others.